Editorial review: American Journal of Sports Medicine “Evaluation of the Risk Factors for a Rotator Cuff Retear After Repair Surgery” - Gates, Stephen; Argo, Madison; Khazzam, Michael (Annals of Joint, 2017)
With reported retear rates of 17–19% in recent large cohorts following arthroscopic rotator cuff repair surgery, identification of risk factors leading to retears is of significant prognostic value (1,2).